KAJIAN PRODUKSI ENERGI HIDROGEN MENUJU TRANSISI EKONOMI BEBAS CO2 : SEBUAH TINJAUAN PUSTAKA - Sutarno Sutarno; Abdul Malik (Teknoin, 2016)
The energy demand of the world is foreseen to be increased due to improvements on the living standard of developing countries and the development of global economy. The increase in sustainability of energy supply must be considered as a must to avoid spoiling natural resources for the next human generations and more dramatic effects such as global atmospheric warming. The utilization of CO2-free energy sources, as renewable energy, is one of the most promising way. Nevertheless, massive energy production with such energy sources are far from being practically feasible in short-medium term and an innovative solution should be put implemented CO2. This general assumption is also applicable to any energy carrier such as hydrogen or electricity. In this paper, analysis of the hydrogen production processes conducted and the discussion of the need to develop a CO2- free production scheme like methane cracking is shown